2023
DOI: 10.1242/dev.201642
|View full text |Cite
|
Sign up to set email alerts
|

Axon guidance genes control hepatic artery development

Abstract: Earlier data on liver development demonstrated that morphogenesis of the bile duct, portal mesenchyme and hepatic artery is interdependent, yet how this interdependency is orchestrated remains unknown. Here, using 2D and 3D imaging, we first describe how portal mesenchymal cells organize to form hepatic arteries. Next, we searched for intercellular signalling active during portal area development and found that axon guidance genes are dynamically expressed in developing bile ducts and portal mesenchyme. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Lower expression of HNF1β in ductal plates of inv mice at P0 might be related to the hepatic artery dilation. Because Gannoun et al (2023) have demonstrated that deficient signaling of roundabout 2 (ROBO2)/SLIT2 in the portal mesenchyme, which may be involved in axon guidance, reduces maturation of the vascular smooth muscle cells that form the tunica media of the hepatic artery, this signaling may play an important role in the hepatic dilation in inv mice. In any event, tissue elements of the intrahepatic bile ducts, hepatic artery, and portal veins can interact with one another to form the portal triad.…”
Section: Portal Triad Formationmentioning
confidence: 99%
“…Lower expression of HNF1β in ductal plates of inv mice at P0 might be related to the hepatic artery dilation. Because Gannoun et al (2023) have demonstrated that deficient signaling of roundabout 2 (ROBO2)/SLIT2 in the portal mesenchyme, which may be involved in axon guidance, reduces maturation of the vascular smooth muscle cells that form the tunica media of the hepatic artery, this signaling may play an important role in the hepatic dilation in inv mice. In any event, tissue elements of the intrahepatic bile ducts, hepatic artery, and portal veins can interact with one another to form the portal triad.…”
Section: Portal Triad Formationmentioning
confidence: 99%